2018
DOI: 10.1093/icvts/ivy152
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of routine computed tomography in the evaluation of penetrating war injuries to the chest

Abstract: CXRs continue as the primary diagnostic modality in the assessment of patients with penetrating war injuries to the chest. Chest CTs can be omitted in most patients, thus reducing CT imaging case-load substantially, while most clinically significant chest injuries remain sufficiently recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 38 publications met the inclusion criteria of this systematic review as shown in Figure 1 10–47. There was no other systematic review on this area of research found.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 papers which documented the site of injury, only three were not specific to the injured anatomical region, allowed subcategorisation according to the AIS regions and were not case studies 12 16 27. Eighteen papers were site specific 10 13 18–22 24–26 28 29 33 38 39 42 44 46. Four could not be categorised in relation to the AIS 14 31 43 45.…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of lung injuries are also associated with trauma to other thoracic structures. 3,4 Different degrees of severity of pulmonary laceration and hernia are examples of trauma to the pulmonary parenchyma. 4,5 Injuries of the pleural space (pneumothorax and hemothorax) are frequently associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…Rupture of the diaphragm, sternum fracture, sternoclavicular luxation, scapula fracturs and an unstable thorax are manifestations of contusive trauma to the thoracic wall. 3 Two-thirds of patients with multiple injuries have internal chest injuries and severe chest trauma is associated with polytrauma in 70 to 90% of cases. 1,6 The aim of the present study was to compare open and closed treatment for chest injuries according to mortality, hospitalization, trauma indices and physiological data.…”
Section: Introductionmentioning
confidence: 99%